2018
DOI: 10.1080/01443615.2017.1419462
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after surgical repair of pelvic organ prolapse with Elevate Prolapse Repair System

Abstract: Female pelvic organ prolapse (POP) is a common condition and the correction of prolapse remains a major challenge for the surgical community. A retrospective study of women with POP undergoing pelvic reconstructive surgery with the Elevate System followed-up for 48 months. A total of 138 women with POP were included in the study. We observed an objective cure rate of 94.9% for the anterior wall after 4 years' follow-up. The subjective cure rate was 97.1%. Improvement in the urinary symptoms was seen after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
4
4
0
2
Order By: Relevance
“…Whether a mesh-aided surgical treatment of the posterior compartment can decrease the rate of recurrence even further here should be investigated in additional studies. Overall, this rate of recurrence, as other studies on mesh-aided prolapse surgery have shown 11 , 44 , 46 , is superior to that of autologous tissue reconstruction in the sense of anterior colporrhaphy 3 , 7 . Most of the 19 documented adverse events which occurred during the 12-month follow-up observation period can be attributed to the typical complications following surgical prolapse correction, e.g.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Whether a mesh-aided surgical treatment of the posterior compartment can decrease the rate of recurrence even further here should be investigated in additional studies. Overall, this rate of recurrence, as other studies on mesh-aided prolapse surgery have shown 11 , 44 , 46 , is superior to that of autologous tissue reconstruction in the sense of anterior colporrhaphy 3 , 7 . Most of the 19 documented adverse events which occurred during the 12-month follow-up observation period can be attributed to the typical complications following surgical prolapse correction, e.g.…”
Section: Discussionmentioning
confidence: 53%
“…However, the data on quality of life, sexuality, and the complications presented here give an indication that, with the further development of implants, the surgical treatment of pelvic organ prolapse with the implantation of an alloplastic mesh has had fewer complications and has become more satisfactory for patients with regard to the postoperative quality of life, including sexuality. In the past 3 years, short-term as well as long-term data on vaginal mesh implantations have been continuously published 43 , 44 , 45 , 46 , 48 . This shows that this surgical method represents a treatment which is currently widely used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The better QoL scores compared to baseline scores were also observed in all the 3 P-QoL components (PC, PSC and PRC) after 6 months. Previous studies in Western countries using P-QoL instrument also con rmed that correction of POP via alloplastic vaginal meshes can signi cantly improve patients' QoL [24,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 84%